Survey of Passenger Ships – Instructions to Surveyors - Anonymous (Her Majesty's Stationery Office, 1961)
These Instructions are issued by the Ministry of Transport for the guidance of their Marine Surveyors in surveying passenger ships under the provisions of the Merchant Shipping Acts. They also indicate to shipowners, shipbuilders and others concerned the procedure which the Department adopts for the survey of passenger ships, and the conditions under which Passenger and Safety Certificates and Passenger Certificates are issued. These instructions should be read in conjunction with the other volumes of the Ministry’s Instructions to their Marine Surveyors on the subject of life-saving appliances, fire appliances, load line, radio, direction finders, lights, shapes and sound Signals, and pilot ladders. Separate publications are also available covering the statutory provisions for tonnage measurement, crew accommodation, musters and drills and the marking, stowage and carriage of dangerous goods.
ERAF: A3.P34
Keywords: passenger ship; Fire; survey; instructions